Identification of lncRNAs Associated With Neuroblastoma in Cross-Sectional Databases: Potential Biomarkers - Prajapati, Bharat; Fatma, Mena; Fatima, Mahar; Khan, Md Tipu; Sinha, Subrata; Seth, Prahlad K. (Frontiers in Molecular Neuroscience, 2019)
Long non-coding RNAs (lncRNAs) have emerged as an important regulatory control in biological systems. Though the field of lncRNA has been progressing rapidly, a complete understanding of the role of lncRNAs in neuroblastoma pathogenesis is still lacking. To identify the abrogated lncRNAs in primary neuroblastoma and in the metastasized as well as the relapsed form of neuroblastoma, we analyzed an RNA-seq dataset on neuroblastoma that is available online to identify the lncRNAs that could potentially be contributing to the biology of neuroblastoma. The identified lncRNAs were further scrutinized using a publicly available epigenetic dataset of neuroblastoma and a cancer database. After this cross-sectional study, we were able to identify three significant lncRNAs, CASC15, PPP1R26-AS1, and USP3-AS1, which could serve as potential biomarkers in clinical studies of neuroblastoma pathogenesis.